International migration and dietary change in Mexican women from a social practice framework. (1st June 2018) - Bojorquez, Ietza; Rosales, Cecilia; Angulo, Alexandra; de Zapien, Jill; Denman, Catalina; Madanat, Hala
Abstract: Migration from lower- and middle-income to high-income countries is associated with dietary change, and especially with the adoption of a modern, less healthy diet. In this article we analyze the dietary changes experienced by Mexican migrants, employing as a theoretical framework the concept of social practice. According to this framework, practices integrate material elements, meanings and competences that provide their conditions of possibility. Practices are shared by members of social groups, and interact with other competing or reinforcing practices. Between 2014 and 2015, we conducted semi-structured interviews with 27 women, international return migrants living in Tijuana, Mexico. The interview guide asked about history of migration and dietary change. We found three main areas of dietary change: from subsistence farming to ready meals, abundance vs. restriction, and adoption of new food items. The first one was associated with changes in food procurement and female work: when moving from rural to urban areas, participants substituted self-produced for purchased food; and as migrant women joined the labor force, consumption of ready meals increased. The second was the result of changes in income: participants of lower socioeconomic position modified the logic of food acquisition from restriction to abundance and back, depending on the available resources. The third change was relatively minor, with occasional consumption of new dishes or food items, and was associated with exposure to different cuisines and with learning how to cook them. Public health efforts to improve the migrants' diets should take into account the constitutive elements of dietary practices, instead of isolating individuals from their social contexts.